Pemberdayaan Ekonomi Kelompok Wanita Nelayan Melalui Pengolahan Produk Ikan Ambu (Istiophoriformes Sp) dan Edukasi Konsep Frugal Living Financial di Desa Bonde, Kecamatan Pamboang - sriutami permata (MALLOMO: Journal of Community Service, 2025)
Desa Bonde, located in Pamboang District with an area of 3.47 km², is a coastal village with abundant marine resources, particularly the Ambu fish (Istiophoriformes sp). This fish is endemic to Pamboang waters, known for its high protein and nutritional value, yet it remains underutilized by the local community. The main issues faced by the community are the lack of knowledge and skills in processing fishery products, especially Ambu fish, as well as limited awareness and understanding of prudent financial management. The Community Partnership Stimulus Program (PKMS) offers solutions through Training on processing Ambu fish into economically valuable products such as fish-based empek-empek and nuggets, and Education and training on the concept of Frugal Living Financial for better financial management. The program is carried out in three main stages: preparation, product processing training, and financial management education. The expected outcomes of this program include publication in a nationally accredited Sinta journal, coverage in electronic mass media, and a documentary video of the activities. This program aims to enhance the community's skills and understanding, as well as promote economic independence based on local potentialtik